Iron Ore Tailings as Partial Replacement for Fine Aggregate in Concrete Production – Review - Abdulaziz Alhassan; Kudirat O. Yusuf; Adavi Aliyu Abdulazeez; Salihu Usman (International Journal of Engineering and Management Research, 2022)
Normal River sand is one of the major components of concrete, generally termed fine aggregate. A large volume of sand is needed annually for construction work globally. Mining or extraction of sand from the river bed, ocean beds, beaches, and inland dunes is accompanied by several problems such as; lowering of the water table, sinking of bridge piers and erosion of river bed and instability of river bed on the environment, etc. To decrease these environmental impacts and the cost of conventional fine aggregates, alternative materials like mining waste have been studied by several researchers to replace partially fine aggregates in concrete production. Iron ore tailings (IOT) are one of the mining wastes obtained from the beneficiation process of iron ore concentrates. This paper presents an overview of the work carried out on the use of IOT as a partial replacement of fine aggregate in concrete and its effects on the workability, mechanical, and durability properties of concrete.